PERFORMA PERTUMBUHAN UDANG VANAME (Litopenaus vannamei) PADA SALINITAS BERBEDA - Lestari, Fingki Yuni; Haris, Abdul; Rahmi, Rahmi; Hamsah, Hamsah; Akmaluddin, Akmaluddin (Jurnal Ruaya : Jurnal Penelitian dan Kajian Ilmu Perikanan dan Kelautan, 2023)
ABSTRACT Vannamei shrimp is one type of the Penaeid shrimp group that is able to adapt to high salinity waters of up to 50 g L-1 and also from freshwater waters, especially in juvenile to adult stages (Pan et al. 2007). Vannamei shrimp are included in the category of euryhalin organisms so that they can survive differently, this is in accordance with (Daviss, 2004). Vannamei shrimp have the ability to survive in a wide range of water salinity so that technology development for aquaculture environmental engineering can be carried out in conditions of water salinity that are quite diverse. The high tolerance ability of vaname shrimp to a wide range of salinity values is one of the triggers for increased activity of vaname shrimp farming, especially in some Asia (Shinn et al. 2018; FAO 2018). This study used a completely randomized design (CRD) with 4 treatments with three replications each. As for what was tested for treatment A (25 ppt salinity), B (20 ppt salinity), C (15 ppt salinity), D (10 ppt salinity). The results of different salinity studies showed a significant effect (P